NUV-pumped luminescence of thermally stable samarium-activated alkali metal borophosphate phosphor - Fang, Zhenyu; Yang, Dan; Zheng, Youkui; Song, Jialiang; Yang, Tongsheng; Song, Ruitong; Xiang, Yuefei; Zhu, Jing (Journal of advanced ceramics, 2021)
Exploring outstanding rare-earth activated inorganic phosphors with good thermostability has always been a research focus for high-power white light-emitting diodes (LEDs). In this study, we report a Sm 3+ -activated KNa 4 B 2 P 3 O 13 (KNBP) powder phase. Its particle morphology, photoluminescence properties, concentration quenching mechanism, thermal quenching mechanism, and chromatic properties are demonstrated. Upon the near-ultraviolet (NUV) irradiation of 402 nm, the powder phase exhibits orange-red visible luminescence performance, originating from typical 4 G 5/2 → 6 H J/2 ( J = 5, 7, 9) transitions of Sm 3+ . Importantly, the photoluminescence performance has good thermostability, low correlated color temperature (CCT), and high color purity (CP), indicating its promising application in the NUV-pumped warm white LEDs.